Sugarcane growth through fermented bamboo shoot application - Roniel A. Ardeña; Nyle A. Pardillo; Justine V. Gemida (Northern Negros State College of Science and Technology (NONESCOST), 2022)
This study was conducted to determine the growth of sugarcane (Saccharum officinarum) as affected by fermented bamboo shoot application in terms of plant height, number and diameter of nodes, number of leaves, and average number of tillers. Study results would help farmers to find an alternative source in growth promotant hormone that could find in fermented bamboo shoot (FBS) that is locally available compared to synthetic cytokinin. There were four treatments used: t1- 2 ml synthetic cytokinin/L of water (control); t2- 2 ml of FBS/L of water; t3- 7 ml of FBS/L of water, t4- 12 ml of FBS/L of water. These treatments were arranged in Completely Randomized Design (CRD) and were replicated four times. The Analysis of Variance (ANOVA) was used as a statistical tool of the study and comparison among means using Honest Tukeys Significant difference at 5% level of significance. Sugarcane plants applied with 7 ml bamboo shoot concoctions has highest mean in plant height and number of leaves which is significantly higher than synthetic cytokinin and 2 ml concoction. On the other hand, application of 12 ml concoction got the highest mean in number of nodes and nodes diameter which is statistically higher than synthetic cytokinin and 2 ml concoction but comparable to 7 ml concoction. Based on results, FBS is better source of cytokinin and could be an alternative of using synthetic cytokinin. Results also revealed that using 7 ml and 12 ml concoctions performs better in all agronomic parameters. It is recommended to use FBS as a replacement of using the synthetic cytokinin at the levels of 7 ml and 12 ml concoctions per litre of water. Further study on the effect of FBS must be conducted to determine significance in tiller production of sugarcane. Further research study for the FBS to be analyzed for cytokinin content and will be used as fertilizer to other crops and vegetables are recommended to truly validate the results.